Golgi phosphoprotein 3 (GOLPH3) promotes hepatocellular carcinoma progression by activating mTOR signaling pathway - Liu, Hongying (BMC Cancer, 2018)
BACKGROUND: Hepatocellular carcinoma (HCC) is the sixth most common cancer and the second leading cause of cancer-related deaths worldwide. Despite new technologies in diagnosis and treatment, the incidence and mortality of HCC continue rising. And its pathogenesis is still unclear. As a highly conserved protein of the Golgi apparatus, Golgi phosphoprotein 3 (GOLPH3) has been shown to be involved in tumorigenesis of HCC. This study aimed to explore the exact oncogenic mechanism of GOLPH3 and provide a novel diagnose biomarker and therapeutic strategy for patients with HCC. METHODS: Firstly, the expression of GOLPH3 was detected in the HCC tissue specimens and HCC cell lines. Secondly, RNA interference was used for GOLPH3 gene inhibition. Thirdly, cell proliferation was analyzed by MTT; cell apoptosis was analyzed by Annexin-V/PI staining, Hoechst 33,342 staining and caspase 3/7 activity assay. Fourthly, xenograft tumor model was used to study the function of GOLPH3 in tumor growth in vivo. Finally, western blotting and immunohistochemistry were used to investigate the role of GOLHP3 in the mTOR signaling pathway. RESULTS: Data showed that the mRNA and protein expression of GOLPH3 were up-regulated in HCC tumor tissue and cell lines compared with those of control (P < 0.05). Correlation analyses showed that GOLPH3 expression was positively correlated with serum alpha-fetoprotein level (AFP, P = 0.006). Knockdown GOLPH3 expression inhibited proliferation and promoted apoptosis in HCC cell lines. What’s more, knockdown GOLPH3 expression led to tumor growth restriction in xenograft tumor model. The expression of phosphorylated mTOR, AKT and S6 K1 were significantly higher in HCC tumor tissue and cell lines compared with those in normal liver tissues (p < 0.05). While the phosphorylated mTOR, AKT and S6 K1 were much lower when diminished GOLPH3 expression in HCC cell lines both in vitro and in vivo. CONCLUSION: The current study suggests that GOLPH3 contributes to the tumorigenesis of HCC by activating mTOR signaling pathway. GOLPH3 is a promising diagnose biomarker and therapeutic target for HCC. Our study may provide a scientific basis for developing effective approaches to treat the HCC patients with GOLPH3 overexpression. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12885-018-4458-7) contains supplementary material, which is available to authorized users.